Breaking the icosahedra in boron carbide - Xie, Kelvin Y. (Proc Natl Acad Sci U S A, 2016)
Findings of laser-assisted atom probe tomography experiments on boron carbide elucidate an approach for characterizing the atomic structure and interatomic bonding of molecules associated with extraordinary structural stability. The discovery of crystallographic planes in these boron carbide datasets substantiates that crystallinity is maintained to the point of field evaporation, and characterization of individual ionization events gives unexpected evidence of the destruction of individual icosahedra. Statistical analyses of the ions created during the field evaporation process have been used to deduce relative atomic bond strengths and show that the icosahedra in boron carbide are not as stable as anticipated. Combined with quantum mechanics simulations, this result provides insight into the structural instability and amorphization of boron carbide. The temporal, spatial, and compositional information provided by atom probe tomography makes it a unique platform for elucidating the relative stability and interactions of primary building blocks in hierarchically crystalline materials.